Web-based education and pedagogical technologies : solutions for learning applications - Esnault, Liliane (IGI Publishing, 2008)
"This book presents cutting-edge research on such topics as network learning, e-learning, managing Web-based learning and teaching technologies, and building Web-based learning communities. It provides researchers, practitioners, and decision makers in the field of education with essential, up-to-date research in designing more effective learning systems and scenarios using Web-based technologies"--Resumé vydavatele.
Keywords: počítačem podporovaná výuka; elektronické zdroje; e-learning; virtuální vzdělávání; computer-aided learning; electronic information resources; virtual education; sborníky; příručky; papers of several authors; handbooks, manuals, etc